EVALUASI BRANDING KOTA PAYAKUMBUH SEBAGAI KOTA RENDANG - Syarif Hidayatullah; Ma’ruf; Verinita (Journal Publicuho, 2024)
This study focused to find out the relationship among several aspects such as attitude toward the brand, brand image, brand equity, and brand preference. By using a quantitative approach and online questionnaires were distributed to 143 tourists who had visited the city of Payakumbuh as Kota Rendang in the last 5 years. A purposive sampling technique with several criteria was used to separate unqualified participants, and then the data was analyzed with the Structural Equation Modeling - Partial Least Square (SEM-PLS) technique by assisting Smart-PLS Software's latest version. The result shows that all research expectations are met.